Essays on Entrepreneurial Finance - Schmidt, Christian; Justus Liebig University Giessen (My University, 2025)
Early-stage start-ups face high uncertainty and risk of failure (Cantamessa et al., 2018), making access to traditional financing mechanisms, such as bank loans, particularly challenging (Colombo & Grilli, 2007; Ueda, 2004). Entrepreneurial finance investors fill this gap by providing capital and value-added services tailored to the unique needs and profiles of new ventures. These investors supply high-risk start-ups with critical resources needed to convert innovative ideas into marketable products and services. Beyond funding, they deliver mentorship and access to their networks, increasing the likelihood of success for the new ventures (Bottazzi et al., 2008; Sapienza, 1992). At the same time, funding start-ups is attractive for entrepreneurial finance investors, as they anticipate substantial returns on their investment (Zider, 1998). By supporting and stimulating entrepreneurial activity, start-up investors play an essential role in driving macroeconomic indicators such as economic growth, innovation, and job creation (Samila & Sorenson, 2011). Over the past few decades, the entrepreneurial finance landscape has undergone substantial transformation. Various types of start-up funding, such as corporate venture capital, governmental venture capital, crowdfunding platforms, and accelerators, have emerged alongside more traditional forms like independent venture capital and angel investing (Drover et al., 2017). These developments have not only expanded the range of funding sources but have also made the entrepreneurial finance industry increasingly dynamic, with the rise of new phenomena such as venture capitalist-business angel syndicates or initial coin offerings (Block et al., 2019; Howell et al., 2020). This growing complexity underscores the importance of gaining a deeper understanding of the entrepreneurial finance ecosystem and its underlying mechanisms. As suggested by the title, Essays on Entrepreneurial Finance, this cumulative dissertation aims to explore the multifaceted nature of start-up financing. The dissertation is organized into three core studies, which are presented in Chapters 2 to 4. The papers are structured in a journal-style format, including an abstract, research motivation and objectives, theoretical framework, methodology, results, and a discussion. Each article represents a separate research project and examines a specific type of entrepreneurial finance investor, advancing ongoing debates and offering new insights into the research field. While Study 1 provides a comprehensive overview of venture capital research, Study 2 focuses on start-up financing by established firms, also known as corporate venture capital. Finally, the personal values of business angel investors and (independent) venture capitalists are compared in Study 3. In academic research, the three investor types discussed in this dissertation are regarded as the primary sources of entrepreneurial finance (Drover et al., 2017). Chapter 5 concludes by synthesizing the main findings of the studies, highlighting theoretical contributions and implications, addressing their inherent limitations, and offering suggestions for future research. The initial paper (Study 1) visually maps the intellectual structure of venture capital research through an in-depth co-citation analysis. The growth of venture capital investments in recent decades has been accompanied by a substantial rise in academic publications on venture capital (Nguyen et al., 2021), making the research field increasingly complex. This fragmentation highlights the need to advance our understanding of this dynamic field of research by uncovering, analyzing, and classifying its dominant research areas. Accordingly, Study 1 concerns the following research questions: What is the intellectual structure of venture capital research? What are the predominant research clusters, and how has this research field evolved? By conducting a co-citation analysis with a sample of 1,410 papers, this exploratory bibliometric study identifies three broad research areas (venture capital life cycle, interfirm relationships and knowledge exchange as well as economic and policy perspectives) that also reveal the development of the research field. These three overarching research areas consist of 13 thematic clusters. For each cluster, a comprehensive description is provided, exploring its content, evolution, theoretical background, and interrelationships with other clusters. Furthermore, the study establishes the category of connecting and methodology papers, as some studies cannot be assigned to a specific cluster, but instead integrate ("connect") research topics from at least two different fields of research. Thus, this paper highlights the most important articles within venture capital research, shows how research fields interact with each other, and finally identifies promising avenues for future research. The second essay (Study 2) delves into the largest thematic cluster identified in Study 1, exploring the role of corporate venture capital (CVC) in driving the investing firms’ strategic change. In today’s dynamic business environment, strategic change is essential for firms aiming to sustain a competitive advantage, secure long-term survival, and achieve superior performance (Müller & Kunisch, 2018). This paper examines CVC through the lens of strategic management to assess its effectiveness as a tool for facilitating the strategic change of established companies. Therefore, Study 2 sheds light on the relationship between CVC and strategic change by addressing the following research question: What is the impact of CVC activity on the parent firm's product portfolio and geographic change? Consistent with the principles of interorganizational learning theory (Lane & Lubatkin, 1998), CVC is proposed as a learning mechanism that enables incumbent firms to access new technologies and markets. This quantitative study provides empirical evidence demonstrating that CVC investments stimulate both product portfolio and geographic change, which represent key dimensions of Furthermore, the study emphasizes that the CVC-induced positive change effects diminish with increasing industry and cultural distance, as higher investment uncertainty and risk arise from identifying heterogeneous knowledge. Accordingly, this paper enhances the understanding of CVC-driven interorganizational learning processes and their influence on strategic change. The third study (Study 3) addresses a "white spot" in the co-citation map of our first study, as it examines the psychological attributes of entrepreneurial finance investors. While existing research has explored the observable characteristics and differences between business angels (BAs) and venture capitalists (VCs), their psychological dimensions have largely been neglected (Mitteness et al., 2012; Morrissette, 2007). That is why the following research question is investigated: What personal values do VCs and BAs hold, and how do they differ? Study 3 conducts an empirical analysis of the language used by BAs and VCs on Twitter, providing valuable insights into their psychological profiles. The purpose of this paper is to explore the dominant personal values of both investor types and to identify differences between them, using Schwartz's (1992) value framework. Employing the language-based assessment tool LIWC, the study analyzes and compares the tweets of 500 BAs with those of 478 VCs. The results indicate a substantial degree of commonality between BAs and VCs, with both investor groups showing comparable scores across five value dimensions. However, the study also reveals significant value disparities, with VCs placing more emphasis on the overarching dimension of self-enhancement, scoring higher in power and achievement-orientation values compared to BAs. Regarding the second overarching value dimension, openness to change vs. conservation, the analysis yields unexpected results. While VCs' focus on the value of security aligns with their investment objectives, it was not anticipated that VCs would score higher than BAs on the opposite value of stimulation. Overall, the results suggest that VCs are generally more conservative, risk-averse, and return-oriented, whereas BAs value their autonomy and take on a mentoring role for the start-up team.
Keywords: entrepreneurial finance; venture capital; angel investment; start-up financing; ddc:650